SINTESIS ETILENDIAMIDA DARI METIL ESTER MINYAK BIJI KELOR (Moringa oleifera) MELALUI REAKSI AMIDASI DENGAN ETILENDIAMIN YANG BERFUNGSI SEBAGAI SURFAKTAN - Arif Wardoyo; Daniel Daniel (PROSIDING SEMINAR KIMIA, 2017)
The ethylenediamide synthesis from methyl ester of Moringa oleifera seed oil has been performed by the amidation reaction. The results showed that GC analysis denoted the most dominant composition of oleic fatty acid in 70.72%. The ethylenediamide which has been resulted an acid,was containedof 12.04 mg KOH/gram of Moringa oleifera seed oil, 5.58 mg KOH/gram of saponification number, and 10.72 of HLB practical value. The FT-IR spectrum has provided a peak of specific absorption for the -C=O amide group, -C-N- which represents the specific group of ethylenediamide. OH and CO ester group showed the process of ethylenediamde synthesis has not proceeded perfectly as seen in the differences of practical and theoretical HLB values. Keywords : Moringa oleifera seed oil, esterification, ethylendiamide, HLB.